(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Yoga is a discipline that seers and saints have been practicing since ancient times to bring flexibility to the spine and joints, to keep the muscles of the body pliable and youthful, increase circulation in arteries and strengthen internal organs. And yet, yoga is so much more than this. Yoga has been said to help strengthen the power of concentration, to banish constipation, to relieve stomach disorders, improve muscle coordination and reduce excess body fat. Yoga has also been said to strengthen the mind-body connection, bring calmness and relaxation to mind, enhance self-confidence, strengthen self-discipline and self-resolve, reduce stress anxiety and increase vitality and energy throughout the body. Evidently, it would appear that yoga has extensive benefits and can help us to be a more balanced, relaxed, focused, efficient and effective person. The benefits of yoga can thus be applied to a variety of disciplines including professional sporting athletes. This paper will highlight the benefits for professional athletes through the practice of Yoga and explore how Yoga can significantly enhance their performance. Yoga can help a sportsperson to have evenness of mind and control of their thoughts even during stress andor adversity.Yoga is able to help a person have control over their body through control of their mind. As such, Yoga can play a key role in cultivating mind control and concentration which helps a sportsperson to perform at their peak level. Yoga also helps to reduce stress and anxiety, cultivate self-confidence and self-belief. All of these elements are pivotal to sporting excellence and peak performance. As highlighted above, in order to perform a sporting action efficiently and effectively, a person needs to have a high degree of concentration and focus with a mind that is calm and controlled. Swami Sivananda states the importance of mind control he asserts “without concentration you cannot have success in any walk of life”. Yoga is also beneficial to a professional athlete as it positively contributes to the health and vitality of the body, strengthens internal organs such as the heart, lungs and liver and helps to maintain fitness and agility.